(untitled) (Medical Forum Monthly, 2024)
Objective: To assess the diagnostic accuracy of C - reactive protein (CRP) for the diagnosis of neonatal sepsis while having blood culture as gold standard. Study Design: A descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Department of Pediatrics, Bahawal Victoria Hospital, Bahawalpur, from December 2018 to May 2019. Materials and Methods: A total of 160 full term neonates with suspicion of sepsis fulfilling the inclusion and exclusion criteria were included in the study. Detailed physical and clinical examination was done, and baseline investigations as per hospital criteria were asked. Sensitivity, Specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy of CRP in relation to blood culture were calculated. Results: There were 107 (66.9%) male and 53 (33.1%) female, showing a male to female ratio as 2.01:1. Mean age of the study participants was 5.26 days with a standard deviation of 3.1 days. Blood culture confirmed the presence of sepsis in 77 (48.1%) cases while 82 (51.3%) neonates were found as CRP positive. Sensitivity, specificity, PPV and NPV of CRP in relation to blood cultured for neonatal sepsis were calculated as 81.8%, 77.1%, 76.8%, 82.1% respectively while accuracy of CRP was found as 79.4%. Conclusion: CRP was found to be a precise indicator of sepsis. In neonates who are suspected for sepsis should always be tested for CRP which will help in early prediction and management of such neonates.